Speed of sound bounds, tidal polarizibility and gravitational waves from neutron stars - Margaritis, Ch.; Moustakidis, Ch. C.; Gaitanos, T.; Lalazissis, G. A. (HNPS Advances in Nuclear Physics, 2019)
n/a